Hyper Loop: Conceptual Overview of Hyper Loop Model, Its Futuristic Features and Challenges: Revolutionizing Transportation: The Hyper Loop Concept (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Hyper loop is a Conceptual mode of transportation designed for saving the travel time and traffic jam around the metro cities of the world. The concept deviates from existing high-speed rail designs by eliminating the rails, enclosing the passenger pod in a tube under a partial vacuum, and suspending the pod on air bearings. Existing conventional modes of transportation of people consists of four unique types rail, road, water, and air. These modes of transport tend to be either relatively slow (i.e., road and water), expensive (i.e., air), or a combination of relatively slow and expensive (i.e., rail). Hyper loop is a new mode of transport that seeks to change this paradigm by being both fast and inexpensive for people and goods. Hyper loop is also unique in that it is an open design concept, similar to Linux. Feedback is desired from the community that can help advance the Hyper loop design and bring it from concept to reality.Hyper loop consists of a low pressure tube with capsules that are transported at both low and high speeds throughout the length of the tube. The capsules are supported on a cushion of air, featuring pressurized air and aerodynamic lift. The capsules are accelerated via a magnetic linear accelerator affixed at various stations on the low pressure tube with rotors contained in each capsule. Passengers may enter and exit Hyper loop at stations located either at the ends of the tube, or branches along the tube length.